CONTROL SYSTEM OF ENTERPRISE CASH FLOWS: REQUIREMENTS, ANALYSIS TECHNIQUE AND OPTIMIZATION PROBLEMS - J. E. Gorbach; S. M. Kozlov (Наука и техника)
The paper determines an essence of cash flows and describes enterprise requirements to financial resources. The scheme of enterprise monetary flow movement is considered in the paper. The paper describes technique of the most rational analysis of positive and negative enterprise monetary flows and also a system of their balancing and optimization.